Maternal Nutrition during Early Pregnancy and Cardiometabolic Status of Neonates at Birth - Musarrat Riaz; Fareeha Shaikh; Asher Fawwad; Rubina Hakeem; A. Samad Shera; Graham A. Hitman; Bishwajit Bhowmik; Nayla Christina do Vale Moreira; Abdul Basit; Akhtar Hussain (Journal of Diabetes Research)
Objective. To explore the impact of maternal body weight on maternal nutrition and micronutrient status in early pregnancy and potential impact on metabolic status in newborns. Methodology. The EU FP7 project GIFTS was conducted from Jan 2012 to May 2014. Demographic details and anthropometric measurements of women in the first trimester of pregnancy were obtained. Blood samples were collected for OGTT, insulin, lipid profile, serum folate, ferritin, vitamin D, vitamin B12, and red cell folate. Newborn anthropometric characteristics were observed. Cord blood samples were collected after delivery for glucose, insulin, and lipid profile of newborns. Results. A total of 301 pregnant mothers, 108 overweight, 63 underweight, and 130 normal weight were included. Prevalence of vitamin D deficiency (<30 ng/mL) and low vitamin B12 (<190 ng/l) were high, 44% and 42%, respectively, in the first trimester. Anemic women (due to B12 or iron deficiency) were 79%, while 72% had low ferritin levels. Gestational diabetes was 16%. Differences were observed between underweight and overweight mothers (P<0.05) for fasting blood glucose, insulin levels, and serum ferritin were observed. No significant difference was observed between vitamin D, serum B12, and red cell folate levels. Conclusion. Prevalence of multiple micronutrient deficiencies was common among Pakistani women during early pregnancy despite the nonvegetarian diet that has important implications for pregnancy care in Pakistan and potentially in expatriate communities living abroad. This trial is registered with ISRCTN number 83599025.